ANALISIS BERITA HOAX COVID - 19 DI MEDIA SOSIAL DI INDONESIA - ROCHANI NANI RAHAYU; SENSUSIYATI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
A review of hoax news about Corona Virus was carried out, using data sources from the site https://www.kominfo.go.id/, https://www.suara.com/news, and https://news.detik.com/ news for the period January - March 2020. Search for news based on keywords hoaxes and corona. Furthermore, the search results obtained are grouped according to the research objectives, namely; 1) Topics included in the news; 2) News broadcast period / time 3) Hoax scene. 4) Sites that inform hoax news. Furthermore, the data obtained are made in tabular form, then carried out analysis, discussion and drawing conclusions. The results of the review showed that from the 50 findings of the search results, three news topics were obtained, namely the Corona Virus outbreak, treatment, social behavior in dealing with the virus. The site https://www.kominfo.go.id/, is the site that gives the most warnings to the public about the Corona Virus hoax, while DKI Jakarta is the most mentioned area in hoax reporting, and the most widely disseminated hoax news on March 24, 2020 which is 10 time.